Tìm x :
2009 ( x- 12 ) = 0
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(x.\left(x-2009\right)-2010x+2009.2010=0\)
\(x.\left(x-2009\right)-2010\left(x-2009\right)=0\)
\(\left(x-2009\right)\left(x-2010\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x-2009=0\\x-2010=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=2009\\x=2010\end{cases}}}\)
Vậy \(\orbr{\begin{cases}x=2009\\x=2010\end{cases}}\)
\(a,\)\(\left(5x-15\right)\div5=0\)
\(\Rightarrow x-3=0\)
\(\Rightarrow x=3\)
\(b,\)\(84-4\left(2x+1\right)=48\)
\(\Rightarrow84-8x-4=48\)
\(\Rightarrow8x=32\)
\(\Rightarrow x=4\)
1 . Tìm x :
a , 2009 ( x- 12 ) = 0
<=> \(x-12=-2009\)
<=> \(x= -1997\)
Vậy \(x= -1997 \)
a: =>|x-2009|=2009-x
=>x-2009<=0
=>x<=2009
b: =>2x-1=0 và y-2/5=0 và x+y-z=0
=>x=1/2 và y=2/5 và z=x+y=1/2+2/5=5/10+4/10=9/10
Thấy : 2009(x-12) = )
=> x-12 = 0
=> x = 12
\(\Leftrightarrow\)x-12=0
\(\Leftrightarrow\)x=12